The Effect of initiating corticosteroids on lung function and symptoms in patients with active pulmonary sarcoidosis - Eknewir, Salaheddin (Department of Medicine, 2025)
Background: Pulmonary sarcoidosis can lead to significant morbidity and mortality, and the use of corticosteroids is a common treatment strategy1,2. The expected response to corticosteroids with respect to lung function is highly variable and not studied in an African cohort. The primary objective of our study was to investigate the impact of corticosteroids on lung function in patients with active pulmonary sarcoidosis. Methods: We conducted a retrospective cohort study including all patients with active pulmonary sarcoidosis initiated on systemic corticosteroids documented in the Groote Schuur Hospital respiratory clinic registry. Patients with histologically proven pulmonary sarcoidosis in whom prednisone therapy was initiated were identified retrospectively from the Groote Schuur Hospital respiratory clinic registry. Data extracted from medical records included patient demographics and clinical characteristics, corticosteroid dosage, duration and recorded side effects, chest imaging, and pulmonary function testing across one year following steroid initiation. We analyzed the effect of prednisone on FVC and DLCO trajectory and reported the serial changes at 3 monthly intervals. Data is presented as mean (± SD) unless otherwise specified. Results: The study group comprised 42 patients, 30 females (71%) and 12 males (29%), with a mean age of 41.6 ± 9.8 years. The majority of patients (78.5%) were non-smokers. More than two-thirds of patients (69%) were diagnosed with Scadding II sarcoidosis. Routine lung function monitoring at 3 months showed a significant improvement in FVC with steroid therapy from 70.8(26.2) % to 77.5(25.5) % (mean change 6.3(11.3) %, p<0.001). Although not statistically significant, the FVC continued to improve numerically between month 3 (77.5%) and month 6, 79.0(23.5%). DLCO improved from 57.6(24.9) % at baseline to 61.0(33.0) % at 3 months to 68.9(28.1) % at 6 months (p<0.001) Weight changed over time with a mean (SD) increase of 8.3(7.0)kg at 9 months. Conclusions: Among patients with acute pulmonary sarcoidosis requiring immunosuppression therapy, prednisone improved FVC and DLCO, with most of the FVC effect occurring within 3 months after initiation. DLCO continued to improve to 6 months Weight gain positively correlated with cumulative prednisone dose over 9 months.